(DES)PLUGA: (DIS)PLUG: COMPUTATIONAL THINKING APPLIED TO INNOVATIVE ACTIVITIES (Revista Contexto & Educação, 2021)
Considering the need for the evolution of current teaching methods, this research involves the development of activities that address the concepts of Computational Thinking, involving its four pillars. The activities are divided into two groups: the group of unplugged activities where there is not have the use of machines, and the group of plugged activities where there is the use of digital resources. For this, we followed the action research methodology, with 6 steps: systematic literature review, elaboration, testing, validation, correction and development of the final product, where they will finally reach the students, first through the teachers who will assist the team in the validation stage and later with wide dissemination. So far, around 40 activities have already been developed, and in this article we exemplify the unplugged activities already developed and which are in the validation phase with teachers from the basic school. There was also the opportunity to test some activities in a mini-course with students, who contributed with comments and different views on the methodologies. Throughout the research, it is intended to complete the other steps and assist in the training of teachers in Computational Thinking, innovating the methodologies currently used in the classroom in the face of a generation of digital natives.
Keywords: Unplugged computation; Programming logic; Digital literacy